Artists, Patrons, and the Public: Why Culture Changes - Lord, Barry; Lord, Gail Dexter (Rowman & Littlefield Publishers, 2010)
In this book, Barry and Gail Lord focus their two lifetimes of international experience working in the cultural sector on the challenging questions of why and how culture changes. They situate their discourse on aesthetic culture within a broad and inclusive definition of culture in relation to material, physical and socio-political cultures. Here at last is a dynamic understanding of the work of art, in all aspects, media and disciplines, illuminating both the primary role of the artist in initiating cultural change, and the crucial role of patronage in sustaining the artist. Drawing on their worldwide experience, they demonstrate the interdependence of artistic production, patronage, and audience and the remarkable transformations that we have witnessed through the millennia of the history of the arts, from our ancient past to the knowledge economy of the twenty-first century. Questions of cultural identity, migration, and our growing environmental consciousness are just a few examples of the contexts in which the Lords show how and why our cultural values are formed and transformed. This book is intended for artists, students, and teachers of art history, museum studies, cultural studies, and philosophy, and for cultural workers in all media and disciplines. It is above all intended for those who think of themselves first as audience because we are all participants in cultural change.